Characteristics of coconut fibre combined with vinyl ester composites through material testing and machining - Suhami, Muhammad Wafiuddin; Ab Wahab, Norfariza; Hamzah, Khairum; Paijan, Lailatul Harina; Sasahara, Hiroyuki (Jan Evangelista Purkyne University, 2023)
In today's manufacturing industry, composites are widely used. This is primarily due to the highly variable material properties that can be obtained by combining various materials as reinforcements and matrices. However, modern environmental concerns have pushed researchers and engineers to seek materials from organic and renewable sources. The study will look into composite surface roughness during the cutting process, which will involve milling with a CNC router machine. A portable surface roughness tester will be used to obtain a surface roughness average (Ra) reading, and microscopes will be used to examine the composite surface roughness behaviour under a microscope. Based on the results of the experiment, 82 wt.% vinyl ester resin on coconut fibre composite provides the best material properties. With a constant feed rate of 500 mm/min applied to spindle speeds of 5,000, 20,000, and 30,000 rpm, the 5,000 rpm showed the best surface roughness average performance compared to the other two. Further research focusing on feed rates may be required to better deduce the material machining data.